Effect of sonochemical synthesis on vanadyl phosphate dihydrate (VOPO4.2H2O) - Wong Yee Ching; Y.H. Taufiq Yap; Z.Zainal (2011)
Six vanadyl phosphate dihydrate were prepared via sonochemical synthesis with different duration of time , i.e. 15, 30,45, 90 and 120 min are denoted as DS15, DS30, DS45,DS60,DS90 and DS120, respectively.All these samples were characterized by using X-ray diffraction(XRD), scanning electron microscope (SEM)and transmission electron microscope (TEM).From the XRD patterns of the VOPO4.2H2O obtained via sonochemical synthesis at different time duration perfectly matched that of the standard VOPO4.2H2O, indicating the high purity of the VOPO4.2H2O produced through this technique which drastically reduced the synthesis time to only 15 min instead of up to 24 h when compared to the conventional reflux method. The monographs obtained from SEM and TEM showed that DS120 produced a much more unifom plate-like structure and are stacjed to rach other to form a layered structure with diameters of 1000nm.